Asylum claims based on sexual orientation: a review of psycho-legal issues in credibility assessments - Selim, Hedayat (Psychology, crime & law, 2023)
The number of people seeking asylum based on their sexual orientation is expected to continue increasing. Assessing the credibility of such claims to determine whether asylum-seekers meet the criteria for refugee status is a complex task for asylum officials. These assessments involve several psychological aspects, affecting applicants’ disclosure and asylum officials’ determinations. Here, we present a narrative literature review of 47 original manuscripts to analyze credibility assessments in asylum claims based on sexual orientation. We demonstrate that asylum officials often make assumptions regarding human sexuality, sexual identity formation and sexual behavior that are either partially or entirely unsupported by psychological research. These assumptions are problematic as they undermine the validity of the asylum process and put vulnerable individuals at risk of severe harm. The challenges are aggravated in the cross-cultural context of asylum determinations, where applicants from different countries may manifest their sexual orientation in ways that deviate from Western expectations. We discuss the implications of our review’s findings for psychological research and asylum practice.